Cervical cancer care at a tertiary oncology facility in Uganda: Comparing daily practice with national treatment targets on cervical cancer control. - Marlieke de Fouw; Melissa W M Boere; Carolyn Nakisige; Mariam Nabwire; Jane Namugga; Israel Luutu; Jackson Orem; Jan M M van Lith; Jogchum J Beltman (PLoS ONE, 2025)
Objective Treatment of cervical cancer patients in Uganda is hampered by late diagnosis due to the unavailability of timely screening and limited availability of advanced cancer care. This study evaluated the clinical presentation and management of cervical cancer patients presenting at the Uganda Cancer Institute (UCI) in Kampala, the tertiary oncology facility in Uganda with access to radiotherapy and reflected on daily clinical practice to identify priority areas for improving cervical cancer care in Uganda. Patients and methods We retrospectively analyzed medical records of all cervical cancer patients presenting to UCI between January 2017 and March 2018 for sociodemographic characteristics and clinical variables with descriptive statistics. The clinical management of patients with early and advanced stage disease who initiated treatment at UCI was evaluated using the national targets formulated in the Uganda strategic plan for cervical cancer prevention and control. Results Medical records of 583 patients were included, representing less than 10% of the annual estimated incidence in Uganda. The majority (86%) of patients presented with advanced stage of disease. More than half of patients never initiated (31%) or interrupted (30%) treatment. The national treatment targets for surgery (10%) and palliative care (25%) were achieved for eligible patients at UCI, however, the target for chemoradiotherapy (65%) was not met. Conclusion Daily clinical practice differed from the ambitions formulated in the national treatment targets on cervical cancer control. While most women presented in advanced stage requiring chemoradiotherapy, the target was not met due to limited availability of radiotherapy. Although targets for surgery and palliative care were achieved at UCI facility level, they mask the unmet need of the majority of cervical cancer patients who never initiated or completed treatment. This demands for further expansion of oncological surgical capacity, chemotherapy and radiotherapy and warrants to focus on accessible prevention programs.